AI-enabled 5G energy-saving technology - Dan XU; Yu ZENG; Weiye MENG; Lika LI (Dianxin kexue)
With the development of 5G commercialization, the number of 5G wireless base station sites has increased sharply, 5G core networks need to be deployed in regions/provinces/cities data centers, as well as the data centers were developing on a larger scale, the problem of energy consumption was becoming increasingly prominent.Based on the main proportion of energy consumption in the whole network, the energy efficiency evaluation methods of 5G access network, core network and data center was investigated.The AI-enabled energy-saving technology of base stations and pilot application scheme, 5G core network energy-saving methods by using AI, as well as the AI-enabled energy-saving technology of data centers and pilot application scheme were introduced, and the challenges and future research directions of energy-saving technology were finally discussed.The summary and prospect on the energy-saving technology of the overall communication system, will help to improve the understanding of energy efficiency and green network development.